1995
DOI: 10.1063/1.113603
|View full text |Cite
|
Sign up to set email alerts
|

Bond-structure changes of liquid phase deposited oxide (SiO2−xFx) on N2 annealing

Abstract: Fluorine can be naturally incorporated into the silicon oxide (SiO2−xFx) prepared by the liquid phase deposition (LPD) method at 35 °C. Fourier transform infrared and x-ray photoelectron spectroscopy spectra show that an annealing treatment can change its bond-structure. Changes in properties accompanying the restructuring are also observed. The annealing also densifies the LPD oxide and reduces its thickness because Si–F intensity decreases and the Si–O–Si intensity increases as annealing temperature increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Usami et al [3,4] observed the dielectric constant of an ECR-CVD grown SiOF film to be as low as 3.5 and attributed this low value to chemical bonding between Si and Homma et al [5] reported a SiOF film, grown at room temperature by catalytic chemical vapour deposition, having a large density, small residual stress, and a low dielectric constant of about 3.7. SiOF films grown by liquid phase deposition (LPD) have been observed to change in density and bonding structures with changing annealing conditions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Usami et al [3,4] observed the dielectric constant of an ECR-CVD grown SiOF film to be as low as 3.5 and attributed this low value to chemical bonding between Si and Homma et al [5] reported a SiOF film, grown at room temperature by catalytic chemical vapour deposition, having a large density, small residual stress, and a low dielectric constant of about 3.7. SiOF films grown by liquid phase deposition (LPD) have been observed to change in density and bonding structures with changing annealing conditions [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is superior to other deposition methods in terms of the following characteristics: low processing temperature, simple equipment, high growth rate and low cost, and thus has attracted plenty of theoretical and industrial interest. [4][5][6][7][8][9][10][11][12][13] The deposition mechanism of LPD is not understood very thoroughly, 14 despite a Raman spectroscopic study of the H 2 SiF 6 growth solution. 15 This notwithstanding, the technique of LPD has been extended to formation of other oxides, including those of Ti, Sn, Zr, V, Cd, Zn, Ni and Fe.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have investigated liquid-phase deposition (LPD) technology, [21][22][23][24] and applied it to the gate insulator of thin-film transistors (TFTs). 25,26 Many physical and chemical characteristics, such as Auger electron spectroscopy (AES) analysis, 21,22 Fourier transform infrared (FTIR) spectra, 22,24 X-ray photoelectron spectroscopy (XPS) measurement, 24 extraction of interface trap, 25 film stress measurement, 23 stress hysteresis, 23 etc., for LPD dielectric films have been surveyed and analyzed in our proposed papers. [21][22][23][24][25] The LPD technique has also been applied to form the interlayer dielectric (ILD) in multilevel tungsten interconnect structures.…”
mentioning
confidence: 99%
“…25,26 Many physical and chemical characteristics, such as Auger electron spectroscopy (AES) analysis, 21,22 Fourier transform infrared (FTIR) spectra, 22,24 X-ray photoelectron spectroscopy (XPS) measurement, 24 extraction of interface trap, 25 film stress measurement, 23 stress hysteresis, 23 etc., for LPD dielectric films have been surveyed and analyzed in our proposed papers. [21][22][23][24][25] The LPD technique has also been applied to form the interlayer dielectric (ILD) in multilevel tungsten interconnect structures. 28 These studies confirm that LPD oxide possesses excellent electrical properties, low dielectric constant (k) 22 and low stress.…”
mentioning
confidence: 99%